1997
DOI: 10.1007/s002619900267
|View full text |Cite
|
Sign up to set email alerts
|

Widespread use of MRI in gynecology: a myth or reality?

Abstract: It has been 15 years since magnetic resonance imaging (MRI) has been introduced into clinical practice. MRI of the central nervous system (CNS) and musculoskeletal system is flourishing. In the field of gynecology, the medical literature is flooded with evidence and support for the excellence of MRI and its superiority over other imaging modalities. Furthermore, the scientific data are complemented by cost-effectiveness studies to a much greater extent than that of CNS. National surveys, however, show that MRI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0
8

Year Published

1999
1999
2009
2009

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 57 publications
(91 reference statements)
0
3
0
8
Order By: Relevance
“…Due to its superior soft-tissue resolution and multiplanar capability, MR imaging provides a “one-stop” assessment of local disease extent [6,8] . MR should be performed as part of the pre-treatment evaluation for tumors larger than 2 cm, in endocervical lesions, and in obese or pregnant patients [9] .…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…Due to its superior soft-tissue resolution and multiplanar capability, MR imaging provides a “one-stop” assessment of local disease extent [6,8] . MR should be performed as part of the pre-treatment evaluation for tumors larger than 2 cm, in endocervical lesions, and in obese or pregnant patients [9] .…”
Section: Imaging Modalitiesmentioning
confidence: 99%
“…MR imaging provides the most benefit in evaluating tumors greater than 2 cm at clinical examination, endocervical lesions, possible parametrial extension, and pregnant patients [8]. Although a body coil has been shown to provide comparable staging accuracy, use of a phased-array coil increases resolution and decreases the time required for the examination [9].…”
Section: Mr Imaging Techniquementioning
confidence: 99%
“…58 Various studies have found that the accuracy of MRI in differentiating benign from malignant masses ranges from 83% to 99% compared with 53% to 88% for ultrasound and 66% to 94% for CT. 45,59Y63 Magnetic resonance features that are indicative of malignancy include lesion size of greater than 4 cm, solid or predominantly solid mass, vegetations or nodularity in the cyst wall or septa in a cystic lesion, and the presence of ascites, lymphadenopathy, or peritoneal, mesenteric, or omental disease. 1,64,65 Although MRI is not routinely used for staging ovarian cancer, its accuracy in staging is comparable to that of CT, approaching 90%. 58,66 Computed tomography already has an established role in ovarian cancer management and has the benefit of being able to rapidly assess upper abdominal, pleural, and pulmonary disease.…”
Section: Ovarian Cancermentioning
confidence: 99%